DETERMINAN MAHASISWA AKUNTANSI MELAKUKAN KECURANGAN AKADEMIK : STUDI LITERATUR - sopian sopian; nurmala ahmar (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2023)
Academic fraud is a growing topic for the scholars in the field of accounting study in Indonesia. Many factors can encourage individuals to commit academic fraud. This research aims to conduct a literature study based on existing research results to explore various determinant factors that can encourage accounting study program students to commit academic fraud. The results of the literature study found that the theories used by Indonesian scholars were the fraud triangle theory and the fraud diamond theory with quantitative methods. Meanwhile, international scholars use a mix of fraud triangle theory and theories from the other disciplines such as psychology, criminology and law. The methods used are quantitative, qualitative, a mix of quantitative and qualitative and experimental research methods. The results of the literature study are expected to provide ideas and initiatives for academics to develop research on the topic of academic fraud with a theoretical mix between accounting theory and other theories from psicology, criminology and law and priorities the use of various research methods such as a quantitative and qualitative method and experimental method.